Mating system variation and assortative mating of sympatric bromeliads (Pitcairnia spp.) endemic to neotropical inselbergs - Palma-Silva, Clarisse [UNESP]; Cozzolino, Salvatore; Paggi, Gecele Matos; Lexer, Christian; Wendt, Tania (Botanical Soc Amer Inc, 2015)
Premise of the study: The mating system is an important component of the complex set of reproductive isolation barriers causing plant speciation. However, empirical evidence showing that the mating system may promote reproductive isolation in co-occurring species is limited. The mechanisms by which the mating system can act as a reproductive isolation barrier are also largely unknown.Methods: Here we studied progeny arrays genotyped with microsatellites and patterns of stigma-anther separation (herkogamy) to understand the role of mating system shifts in promoting reproductive isolation between two hybridizing taxa with porous genomes, Pitcairnia albiflos and P. staminea (Bromeliaceae).Key results: In P. staminea, we detected increased selfing and reduced herkogamy in one sympatric relative to two allopatric populations, consistent with mating system shifts in sympatry acting to maintain the species integrity of P. staminea when in contact with P. albiflos.Conclusions: Mating system variation is a result of several factors acting simultaneously in these populations. We report mating system shifts as one possible reproductive barrier between these species, acting in addition to numerous other prezygotic (i.e., flower phenology and pollination syndromes) and postzygotic barriers (Bateson-Dobzhansky-Muller genetic incompatibilities).
Keywords: Asymmetric introgression; Breeding system; Bromeliaceae; Evolution of selfing; Herkogamy; Hybridization; Progeny array; Reinforcement; Reproductive isolation; Reproductive biology; Speciation